Gender trait preferences among smallholder cowpea farmers in northern Ghana: lessons from a case study - Jinbaani, Alhassan Nuhu; Owusu, Emmanuel Yaw; Mohammedm Abdul-Razak; Tengey, Theophilus Kwabla; Mawunya, Michael; Kusi, Francis; Mohammed, Haruna (Frontiers Media, 2023)
Introduction: This case study reports on how a gender responsive breeding program contributes to meeting the trait preference of men and women for improved cowpea varieties in northern Ghana.